Livelihood adaptation strategies of farming households to land acquisition: A case study in Vietnam - Nguyen To-The; Linh Nguyen-Thi-Thuy; Phuong Bui-Thi-Thu; Ashfaq Ahmad Shah; Anh Dao-Mong; Quynh Pham-Ngoc-Huong; Linh Pham-Thi; Huong Nguyen-Thi-Lan (Journal of Water and Land Development, 2024)
The livelihoods of households affected by land acquisition in rural Vietnam are crucial for sustainable development and community resilience. This study employs the sustainable livelihoods approach, which recognises the interconnectedness between various factors shaping livelihood outcomes, to investigate factors behind livelihood changes among 474 farm households affected by land acquisition in rural Vietnam. By applying Multinomial Logit (MNL) regression, this paper delves into how personal and household characteristics influence the transition from farming to non-farming activities in agrarian settings. Our findings reveal the diverse and multifaceted impacts of various factors such as gender, age, educational level, household size, household labour force, and the extent of land loss on livelihood strategy choices. This study offers nuanced insights that can guide policymakers and practitioners to design effective interventions that promote sustainable livelihoods and enhance community resilience amidst the challenges posed by land acquisition and rural transformation.